The Effect of Company Size and Profitability on Audit Delay - Nadella Rahmadani; Mahameru Rosy Rochmatullah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the effect of company size and profitability on audit delay in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020–2022. Using a quantitative approach with secondary data from financial reports and purposive sampling, the study analyzed 114 observations through multiple linear regression after classical assumption tests. Audit delay is measured by the number of days between the fiscal year-end and the audit report date; company size is proxied by the natural logarithm of total assets, and profitability by Return on Assets (ROA). The results show that company size negatively affects audit delay, where larger firms tend to complete audits faster due to better internal controls and greater public pressure, aligning with agency and signaling theories. Profitability also influences audit delay, as higher ROA is associated with shorter delays, though the ambiguous effect of low ROA suggests possible non-linear relationships. The study acknowledges limitations, such as the exclusion of control variables like audit firm size, leverage, and firm age, and highlights the contextual relevance of the COVID-19 pandemic, which may have disrupted audit timelines. These findings provide practical insights for auditors, regulators, and stakeholders on factors influencing audit timeliness.